Aplicación del marketing digital y su relación con la rentabilidad de la empresa Casa Bella - Tueros Tinoco, Camilla Nicole (2022)
The objective of the research was to determine the influence of the application of Digital Marketing on the profitability of the Casa Bella company. The methodology used was based on a mixed approach study due to the correlation level between the variables Digital Marketing and Profitability of the company Casa Bella, and with a non-experimental design. The final sample is made up of 328 clients of the company, who are over 18 years of age and was carried out through Google Forms. The importance of the consumer environment in times of COVID-19 is highlighted, as it generated changes in purchasing habits, specifically preferences for digital purchases when searching for product information by digital means to make a better purchase decision. This opportunity generates a greater reach to the target audience through the use of digital media, social networks and e-commerce since they help you capture real and potential customers due to the frequency of use of these digital marketing variables, enhancing the image of the company by having a greater online presence generates interaction with customers and a greater number of purchases, since customers recognize the company through digital media such as social networks or e-commerce, they can purchase the product online or in person as they offer the necessary information about the products and the company. It is concluded that there is a relationship between digital marketing and the profitability of the Casa Bella company, which generates the opportunity to increase customer purchases with the help of digital media, with efficient management to make better decisions.